2019
DOI: 10.3389/fpls.2019.00935
|View full text |Cite
|
Sign up to set email alerts
|

Marchantia polymorpha, a New Model Plant for Autophagy Studies

Abstract: Autophagy is a catabolic process for bulk and selective degradation of cytoplasmic components in the vacuole/lysosome. In Saccharomyces cerevisiae, ATG genes were identified as essential genes for autophagy, and most ATG genes are highly conserved among eukaryotes, including plants. Although reverse genetic analyses have revealed that autophagy is involved in responses to abiotic and biotic stresses in land plants, our knowledge of its molecular mechanism remains l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 143 publications
(198 reference statements)
4
27
0
Order By: Relevance
“…For instance, atg5 and atg7 mutants were inoculated with cauliflower mosaic virus (CaMV) and exhibited more severe symptoms than the wild type, indicating that the process of autophagy may involve an antiviral mechanism (Hafrén et al, 2017). In recent years, the clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated9 (Cas9) (CRISPR/Cas9) system was developed for genome editing (Doudna and Charpentier, 2014;Ma et al, 2016), allowing the scientific community to obtain atg mutants in different species and therefore promoting the study of the function and mechanism of autophagy (O'Prey et al, 2017;Norizuki et al, 2019).…”
Section: Silencing or Mutation Of Atgs In Plantsmentioning
confidence: 99%
“…For instance, atg5 and atg7 mutants were inoculated with cauliflower mosaic virus (CaMV) and exhibited more severe symptoms than the wild type, indicating that the process of autophagy may involve an antiviral mechanism (Hafrén et al, 2017). In recent years, the clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated9 (Cas9) (CRISPR/Cas9) system was developed for genome editing (Doudna and Charpentier, 2014;Ma et al, 2016), allowing the scientific community to obtain atg mutants in different species and therefore promoting the study of the function and mechanism of autophagy (O'Prey et al, 2017;Norizuki et al, 2019).…”
Section: Silencing or Mutation Of Atgs In Plantsmentioning
confidence: 99%
“…In land plants (embryophytes), core ATG genes are highly conserved, and their functions are shown to be similar to homologs in yeast and mammals (Avin-Wittenberg et al, 2012;Yoshimoto, 2012;Norizuki et al, 2019). Studies of Arabidopsis thaliana atg mutants have demonstrated that autophagy is involved in responses to abiotic and biotic stressors such as nutrient starvation and pathogen attacks (Marshall and Vierstra, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…28,29 This drastic organelle remodeling during spermiogenesis could be completed through activated degradation pathways such as autophagy; therefore, we examined whether spermiogenesis in M. polymorpha involves autophagy. We previously reported that Mpatg mutants exhibit chlorosis and hypersensitivity to nutrient starvation, 17 but the involvement of autophagy in reproductive processes remained unassessed. In this study, we investigated whether mutants defective in autophagy also exhibit any defects in spermiogenesis.…”
Section: Autophagy Plays Essential Roles In Normal Spermiogenesismentioning
confidence: 99%
“…In this study, we investigated whether mutants defective in autophagy also exhibit any defects in spermiogenesis. In contrast to wild-type spermatozoids with elongated helical cell bodies containing thin cylindrical nuclei with trace amounts of cytoplasm, spermatozoids of Mpatg5-1 ge , which was generated using the CRISPR/Cas9 system, 17 harbored abundant cytoplasm and abnormally shaped nuclei that were significantly more circular than wild-type spermatozoids (Figures 4A-4C).…”
Section: Autophagy Plays Essential Roles In Normal Spermiogenesismentioning
confidence: 99%
See 1 more Smart Citation